Three and Six Months of Ketogenic Diet for Intractable Childhood Epilepsy: A Systematic Review and Meta-Analysis - Liu, Xian Yu; Chen, Jing; Zhu, Min; Zheng, Guo; Guo, Hu; Lu, XiaoPeng; Wang, Xiaoyu; Yang, Xiao (Frontiers in Neurology, 2019)
Abstract Objective: The ketogenic diet (KD) has been a significantly effective antiepileptic treatment for intractable childhood epilepsy. The duration of ketogenic diet in intractable childhood epilepsy are still not well defined. We aim to realistically assess spasms remission of a period of three months of ketogenic diet as a predictor of six months duration. Methods: Using PubMed、 Cochrane、Embase、Ovid、Web Of Science、Google Scholar and Conference literature and other sources, articles were searched up to May 20, 2018 to investigate the duration and response to the therapy of KD for intractable childhood epilepsy. Studies inclusion criteria were: (i)definite diagnose of intractable childhood epilepsy, (ii)defined three and six months follow-up time, (iii)classified spasms remission evaluation. In addition, the exclusion criteria were: (i)other main therapy researched, (ii)follow-up time unclear, (iii)seizure reduction unclear. The data extracted by two researchers included proportion of KD duration, remission of spasms, year of publication, author, study design, diet varieties. Findings: The search strategy yielded a total of 542 citations, 18 articles were met the inclusion criteria, included in final analysis with a total of 1062 patients. The rates difference for seizure remission of more than 50% of 3 months and 6 months was -0.01(95% CI: -0.09—0.06). And seizure remission of more than 90% was -0.036(95% CI: -0.090—10.017) and seizures free was -0.031(95% CI: -0.081—0.020). Conclusion: This meta-analysis provides statistical support for a period of three months of ketogenic diet as a predictor of six months duration. And a period of three months of ketogenic diet can be used as a trial period to evaluate the effect of ketogenic diet through seizure reduction and decide whether to do some fine-tune of anticonvulsant pharmacotherapy and KD.